Change Management for Micro, Small, and Medium Enterprises (MSMEs) in the Digital Era - Sri Djatnika Sya'diah (Cita Konsultindo Research Center, 2024)
In the era of globalization and digitalization, change is inevitable in all fields, including MSMEs. MSMEs have a vital role in economic growth, but digital change brings new challenges. This research aims to evaluate change management in the context of digital MSMEs, focusing on the urgency of implementation, the change process, and triggering and inhibiting factors. The literature study method was used to collect data from related literature. Change management in MSMEs involves adaptation to changes in technology, markets, and the business environment. The stages of change involve decision, preparation, launch, implementation, and continuation. Internal and external factors influence the change process, with owner/manager characteristics, type of business, resources, customer demand, competition, innovation, and use of data being key. Principles for initiating change include assessing readiness, identifying strategic direction, rollout, implementation, and continuation. Awareness of the importance of change management in the digital era is the key to survival and development for MSMEs.